Approaches for the evaluation of favorable shale gas areas and applications: Implications for China's exploration strategy. Issue 2 (29th October 2019) - Li, Zhen; Zhang, Jinchuan; Tang, Xuan; Gao, Yu; Huo, Zhipeng; Li, Pei; Liu, Junlan; Gong, Dajian
Abstract: To explore practical approaches for the evaluation of favorable shale gas areas, a structural decomposition analysis with respect to the index system, evaluation criteria, weight determination, and evaluation methods was carried out. Five types of indexes were determined from 25 subindexes that formed the index system, and improved whitenization weight functions are proposed to establish evaluation criteria. The index weights calculated using entropy weight and Euclidean distance methods are consistent, whereas the weights determined by gray relational analysis are significantly affected by the relative number of indexes and evaluation objects, selected mother factor, and resolution coefficient. The significant linear positive correlation between the relative approach degree values calculated using TOPSIS and the scores obtained using fuzzy comprehensive evaluation (FCE) is indicative of a consistent evaluation result, but it should be noted that extreme indicator values can have strong effects on the evaluation using the fuzzy similarity method. Finally, an exploration strategy for China's shale gas is suggested: Areas with weak reformation and relatively low maturity are expected to be favorable for marine shale production in South China, and continental and transitional shale‐bearing basins are promising for the prospecting multiple‐origin shale gas and coal measure gas, respectively. Abstract : An evaluation index system of favorable shale gas areas with hierarchy structure was proposed, and the whitenization weight functions in gray system were improved to establish evaluation criteria. And then, combinative index weights were determined by weights obtained using AHP and entropy weight methods. Typical shale gas blocks in China were evaluated using TOPSIS, fuzzy comprehensive evaluation, and fuzzy similarity methods, and on the basis of the evaluation results, exploration strategies for various types of shale gas were suggested.